Onset of Hyperkalemia following the Administration of Angiotensin-Converting Enzyme Inhibitor or Angiotensin II Receptor Blocker - Hye-Ran Jun; Hyunah Kim; Seung-Hwan Lee; Jae Hyoung Cho; Hyunyong Lee; Hyeon Woo Yim; Kun-Ho Yoon; Hun-Sung Kim (Cardiovascular Therapeutics)
Introduction. In spite of the established importance of detecting angiotensin-converting enzyme inhibitor (ACEI) or angiotensin II receptor blocker- (ARB-) induced hyperkalemia, there have not been many studies on the time of its occurrence. Methods. We retrospectively analyzed electronic medical records to determine the onset time and incidence rate of hyperkalemia (serum potassium>5.5 mEq/L or 6.0 mEq/L) among hospitalized patients newly started on a 15-day ACEI or ARB therapy. Results. Among 3101 hospitalized patients, hyperkalemia incidence was 0.5%–0.9% and 0.8%–2.1% in the ACEI and ARB groups, respectively. However, it was not significantly different among different ARB types. Hyperkalemia’s onset was distributed throughout 15 days, without any trend. Hyperkalemia incidence was 7.3 and 35.1 times higher at 5.5 mEq/L (hazard ratio HR=7.31, 95%confidence interval CI=4.19–12.76, p<0.001) and 6.0 mEq/L (HR=35.11, 95%CI=8.25–149.52, p<0.001), respectively, than the baseline creatinine level. Hyperkalemia incidence in patients with chronic renal failure was 5.7 and 9.2 times higher at 5.5 mEq/L (HR=5.72, 95%CI=3.24–10.12, p<0.001) and 6.0 mEq/L (HR=9.16, 95%CI=4.02–20.88, p<0.001), respectively. Conclusions. It is unlikely that it is necessary to monitor hyperkalemia immediately after administration of ACEI or ARB. However, when prescribed for patients with abnormal kidney function, clinicians should always consider the possibility of developing hyperkalemia.